A case of saddle pulmonary embolus visualized on a transthoracic echocardiography in a 69-year-old female - Dilli Ram Poudel; Smith Giri; Ranjan Pathak; Inyong Hwang; Shadwan Alsafwah (Greater Baltimore Medical Center, 2016)
A 69-year-old female with history of immobilization presented with shortness of breath and generalized weakness and was found to have large saddle pulmonary embolus on CT scan. Further evaluation with a transthoracic echocardiography revealed a moderately enlarged and hypokinetic right ventricle with a pulmonary artery clot of about 1.5 cm seen at the bifurcation while the ultrasound of the legs was negative for deep vein thrombosis.